Effect of formononetin on progressive pulmonary pathologies: multitarget mechanisms and therapeutic prospects - Yan, Dan; Wang, Saibin (Frontiers in Pharmacology, 2025)
Formononetin (FMN), an isoflavone derived from Radix Astragali and red clover, has promising therapeutic potential for a wide spectrum of respiratory diseases, including acute lung injury (ALI), pulmonary arterial hypertension (PAH), chronic obstructive pulmonary disease (COPD), asthma, and pulmonary fibrosis (PF). Mechanistically, FMN alleviates oxidative stress, inflammation, and fibrotic remodelling by activating Nrf2/HO-1, inhibiting NF-κB, and modulating the activity of the TGF-β/Smad signalling pathway. Evidence from cellular and animal studies has shown that FMN attenuates lung injury, prevents vascular remodelling, and slows the progression of fibrosis. However, its clinical translation is hampered by poor solubility, rapid metabolism, and low oral bioavailability, which limit its therapeutic effectiveness. To overcome these challenges, novel delivery systems—such as albumin-based FMN nanoparticles (FMN@BSA nanoparticles)—have been developed to increase the stability, bioavailability, and pharmacological potency of FMN. Despite encouraging preclinical outcomes, further studies are needed to clarify upstream mechanisms and conduct rigorous clinical evaluations. This review highlights the potential of FMN as a novel therapeutic candidate for respiratory diseases by summarizing its mechanisms of action and underscoring the importance of advanced delivery strategies in facilitating its future clinical application.